Spermologus rufus BOHEMAN (COLEOPTERA: CURCULIONIDAE) EGG PHASE - BARRETO, Marliton Rocha; dos ANJOS, Norivaldo (Scientia Agraria, 2001)
To characterize the Spermologus rufus Boheman 1843 (Coleoptera: Curculionidae) egg phase was carried out the study under controlled conditions (T = 24.9+0,9º C; UR = 78.5+5,9% and 12 hours footofase). Pairs of adults (male+female) were placed in Wheaton flasks containing three Araucaria angustifolia seeds each. The seeds were replaced daily when oviposition occurred. Seeds containing eggs were dissected in order to accompany insect development during the egg phase. The eggs are yellowish-white, oblong, membranous, apparently smooth with a transparent corion. The average largest width was 0.63+0.02 mm and the average lenght was 1.06+0.03 mm. The incubation period varied from two to six days and the highest frequency of larval eclosion occurred between the third and the fourth day days of incubation. The mean viability per female was equal to 97.91+1.66% and the mean mortality was 2.07%.